Influence of the Milling Cutter Drill on Implant Placement Accuracy in Partially Guided Surgery: An In Vitro Experimental Study - Ana Raquel Ferreira; Catarina Mendes Fonseca; André Correia; Patrícia Fonseca (Applied Sciences, 2025)
Partially guided implant surgery has emerged as a technique that enhances the precision of implant placement while maintaining surgical flexibility. This in vitro experimental study evaluated the influence of the milling cutter drill on the angular and linear deviations of implant placement in synthetic polyurethane bone models using a partially guided surgical protocol. Additionally, the effects of bone density and implant macrogeometry were assessed. A total of 120 Straumann® implants (BL, BLT, and BLX) were placed in polyurethane blocks simulating four bone densities (D1–D4). Implant positions were virtually planned with coDiagnostiX® (version 10.9) software and executed with or without the use of the milling cutter drill. Deviations between planned and final implant positions were measured at the neck and apex using the software’s “Treatment Evaluation” tool. The use of the milling cutter drill significantly reduced angular deviation (p = 0.007), while linear deviations showed no statistically significant differences. Bone density and implant macrogeometry did not significantly affect angular deviation but influenced linear and 3D deviations. Given that angular deviation may compromise prosthetic fit and biomechanical function, the observed reduction is of potential clinical relevance. These findings indicate that the milling cutter drill enhances angular accuracy in partially guided implant surgery and may improve outcomes in anatomically challenging cases. However, the results should be interpreted within the limitations of this in vitro model, including the absence of soft tissue simulation, intraoral constraints, and inter-operator variability.